Strategy In Improving Study Customers: Baktimakmur Indah Surabaya Rural Bank (BPRS) - Qoriani, Hersa Farida (CV Putra Publisher, 2024)
Sharia banking is currently viral and its name is soaring, including the Baktimakmur Indah Surabaya Rural Bank (BPRS). There are lots of products in BPRS that are of interest to the people of Surabaya. Therefore, so that customers in BPRS continue to grow and not run to other BPRS, there must be an effective strategy to increase customers. The importance of services at BPRS has an impact on increasing customers. With the strategy especially on service or service makes the customer increase. The purpose of this research is to find out and analyze the right service strategy at BPRS Baktimakmur Indah Surabaya. In this study, the research method used is a qualitative approach with a descriptive research type. Data collection techniques using observation techniques, interviews and documentation. The strategy in providing services must be further improved and provide extra services for customers who have long been members of BPRS Baktimakmur Indah Surabaya. BPRS uses strategies in carrying out services, namely the basic strategy which includes BPRS staff must be able to be friendly and communicative when serving customers, and neat appearance is a form of good service to customers and prospective customers. While the main service strategy includes excellent service, responsiveness, honesty, innovation, and credibility.